Building Bridges: HCI, Visualization, and Non-formal Modeling c - Ebert, Achim; van der Veer, Gerrit C.; Domik, Gitta; Gershon, Nahum D.; Scheler, Inga.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This volume constitutes the refereed post-workshop proceedings of two IFIP WG 13.7 workshops on Human-Computer Interaction and Visualization: the 7th HCIV Workshop on Non-formal Modelling for Interaction Design, held at the 29th European Conference on Cognitive Ergonomics, ECCE 2011, in Rostock, Germany, in August 2011 and the 8th HCIV Workshop on HCI and Visualization, held at the 13th IFIP TC 13 Conference on Human-Computer Interaction, INTERACT 2011, in Lisbon, Portugal, in September 2011. The 15 revised papers presented were carefully reviewed and selected for inclusion in this volume. They cover a wide range of topics in the fields of non-formal modeling, visualization and HCI and provide visions from researchers working at or across the borders between these domains that may help develop a holistic cross-discipline.
Teaching Information Visualization Via Creative Design -- Learning HCI and Info Vis in the Open -- How to Investigate Interaction with Information Visualisation: An Overview of Methodologies -- A Participatory Design Perspective on Designing Digital Visualizations and HCI in a Cross-Cultural Context -- Recognizing complexity: Visualization for skilled professionals in complex work situations -- Applying CTA to the Design of SA-oriented Visualizations: Heuristics and Recommendations -- Cognitive Ergonomics in Visualization -- Perception or Pixels: Designing a Visual World from the User Point of View -- Patterns in the Clouds -- The Effects of Clustered Presentation on Tag Cloud Interaction -- Non-formal Techniques for Requirements Elicitation, Modeling and Early Assessment for Services -- We need Non-Formal Methods Based on Formal Models in Interaction Design -- Verbal Use Case Specifications for Informal Requirements Elicitation -- Software Design and New Media Design -- Formal and Visual Tools to Design Mobile and Sensory Interfaces and Interactive Environments -- A Documentation-Centred Approach to Software Design, Development and Deployment -- Evolutionary Software Architecture Visualization: An Evaluation.
Keywords: Computer science; Multimedia information systems; User interfaces (Computer systems).; Computer Science; User Interfaces and Human Computer Interaction; Information Systems Applications (incl. Internet).; Multimedia Information Systems; Electronic books